Digitalizing and Cataloging Islamic Manuscripts in Pesantren - Muhammad Nida Fadlan (Studia Islamika, 2012)
Pesantren has become a vehicle for the ulama to spread Islam. Most importantly, in the past, their purpose was to use pesantren to propagate Islam and use kitabs as teaching materials to their students. The ulama had written various subjects they taught at pesantren on the diverse materials, such as paper, bark, bamboo, palmyra, and so on. Then, they instructed their students to copy the manuscripts so that the Islamic teachings containing on the manuscripts could be read by other Muslims. This process had been part of Islamization in Nusantara through santri-kyai relation and the production of manuscripts.DOI: 10.15408/sdi.v19i1.374